2011
DOI: 10.1590/s1517-83822011000200008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antimicrobial resistance and integrons in Escherichia Coli from Punjab, Pakistan

Abstract: Antimicrobial resistance was studied in Escherichia coli strains isolated from urine samples of 457 patients suffering from urinary tract infection. High prevalence of class 1 integrons (43.56%), sulfamethoxazole resistance genes sul1 (45.54%) and sul2 (51.48%) along with occurrence of quinolone resistance genes was detected in multi drug resistance isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
16
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 13 publications
(26 reference statements)
8
16
1
1
Order By: Relevance
“…In Pakistan, the frequencies of nalidixic acid and ciprofloxacin resistance among the E. coli isolated from UTIs were 84.2% and 36.5%, respectively, which is in agreement with our findings [18]. In addition, a study in China showed the frequency of ciprofloxacin resistance to have increased to 59.4% [19].…”
Section: Discussionsupporting
confidence: 91%
“…In Pakistan, the frequencies of nalidixic acid and ciprofloxacin resistance among the E. coli isolated from UTIs were 84.2% and 36.5%, respectively, which is in agreement with our findings [18]. In addition, a study in China showed the frequency of ciprofloxacin resistance to have increased to 59.4% [19].…”
Section: Discussionsupporting
confidence: 91%
“…As previously noted, class 1 integrons were more prevalent than those of class 2 (Johnson et al , 1998; Muhammad et al , 2011; Patti et al , 2008). Similar to a research by Colgan et al (2011), in our study intI1 gene was more frequently detected among UPEC than commensal E. coli isolates, which may contribute for the occurrence and transmission of MDR among UPEC isolates.…”
Section: Discussionsupporting
confidence: 75%
“…Among EPEC isolates, class 1 integron was significantly associated (Table 2). Class 3 integron was not found in any isolate as reported by other studies (White et al, 2001; Yu et al, 2003; Machado et al, 2005; Skurnik et al, 2005; Su et al, 2006; Vinue et al, 2008; Muhammad et al, 2011; Rezaee et al, 2011). Contradicting to the observation, a single study in Iran showed prevalence of class 3 integron with 26.09% (Kargar et al, 2014).…”
Section: Discussionsupporting
confidence: 70%